Efektivitas Kompetensi Kewirausahaan Kepala Sekolah Untuk Meningkatkan Kesejahteraan Guru Sekolah Dasar - ridhwan ridhwan; Marwan Marwan; Sari Rizki Sari Rizki (STKIP Singkawang, 2026)
Teacher welfare is an important factor in improving the quality of education. Principals play a strategic role in achieving such welfare through the implementation of entrepreneurial competence, which includes the ability to innovate, work hard, build collaborative networks, and manage school resources effectively. This study aims to analyze the effectiveness of principals’ entrepreneurial competence in improving the welfare of elementary school teachers in Kejuruan Muda District, Aceh Tamiang Regency. The research employed a qualitative approach with a descriptive method. The subjects consisted of principals and teachers from three public elementary schools, namely SD Negeri 1 Sungai Liput, SD Negeri 2 Sungai Liput, and SD Negeri Kampung Jawa. Data were collected through observation, in-depth interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The results show that: (1) at the innovation stage, principals were able to create various creative programs such as school-based enterprises, teacher skills training, and productive activities oriented toward improving teacher welfare; (2) at the collaborative networking stage, principals actively built partnerships with school committees, communities, and external stakeholders to expand financial and non-financial support; and (3) at the resource management stage, principals effectively utilized human, material, and financial resources to support programs aimed at enhancing teacher welfare. Thus, principals’ entrepreneurial competence is proven to be effective in improving teacher welfare in terms of economic, professional, and motivational aspects.The research findings contribute to the school program that the principal's entrepreneurial and innovative leadership is an important factor in creating teacher welfare.